Advanced abdominal pregnancy complicated by uterine prolapse: a case report at the issaka gazoby maternity of niamey (niger) - Maimouna Chaibou Yacouba; Hamidou Soumana Diouaga; Maina Oumara; Madeleine Ramatou Garba; Madi Nayama (BMC Pregnancy and Childbirth)
Abstract Background Advanced abdominal pregnancy is a rare form of ectopic pregnancy. It is rarely diagnosed especially in low-income countries and associated with very high fetal and maternal morbidity and mortality. The management of advanced abdominal pregnancy is based on surgical procedure. Laparotomy was chosen to be better than laparoscopic surgery because of the risk of perioperative haemorrhage, which can be uncontrollable from the implantation site. Uterine prolapse during pregnancy is rare. The etiology is multifactorial. We report this association to discuss difficulties in the management of these two pathologies in areas where health services are unavailable or utilized poorly. Patient presentation A 25-year-old woman was referred to our maternity ward for uterine prolapse and pregnancy. On examination, the cervix protruded and edematous beyond the introitus (Stade IV of the POP-Q classification). She had no prenatal consultation and no history of surgery or vaginal delivery complications. The obstetric ultrasound revealed an empty uterus and an abdominal pregnancy at 32 weeks and the placenta localization was unclear. An urgent laparotomy was performed, and we discovered the foetus in the abdominal cavity. The placenta was attached to the right ovary and large ligament. We successfully extracted the foetus and placenta. The newborn presented ectodactylia and club varus equinus. He developed respiratory distress after 12 h and died. Before her was discharged from the hospital, she requested sterilization and total hysterectomy was scheduled after 3 months. Conclusion The association between advanced abdominal pregnancy and uterine prolapse is exceptional. This phenomenon can be observed in developing countries because of poor prenatal follow-up. Management is based on urgent laparotomy for abdominal pregnancy and hysterectomy for uterine prolapse for women who have completed their family’s life.